2020
DOI: 10.3390/cells9102160
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis-Associated MicroRNAs: From Pathogenesis to Disease Biomarkers

Abstract: Tuberculosis (TB) caused by Mycobacterium tuberculosis is one of the most lethal infectious diseases with estimates of approximately 1.4 million human deaths in 2018. M. tuberculosis has a well-established ability to circumvent the host immune system to ensure its intracellular survival and persistence in the host. Mechanisms include subversion of expression of key microRNAs (miRNAs) involved in the regulation of host innate and adaptive immune response against M. tuberculosis. Several studies have reported di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 119 publications
0
56
0
1
Order By: Relevance
“…It plays a crucial role in pulmonary fibrosis [ 53 ]. However, another report found the down-regulation of miR-21 in plasma samples [ 54 ]. miR-193 was up-regulated in PBMCs and serum samples in tuberculosis patients [ 20 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…It plays a crucial role in pulmonary fibrosis [ 53 ]. However, another report found the down-regulation of miR-21 in plasma samples [ 54 ]. miR-193 was up-regulated in PBMCs and serum samples in tuberculosis patients [ 20 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…The induction of a robust yet controlled inflammatory response plays a key role in the containment and eradication of the infection at an early stage. It was found that Mtb suppresses inflammation via the upregulation of miR-21-5p, miR-27b-3p, miR-99b-5p, miR-125-5p, miR-146a-5p, miR-223-3p, and the downregulation of let-7f, miR-20b-5p and miR-142-3p ( 18 ). Mtb HN878 infection of monocyte-derived macrophages (MDMs) induces the expression of the pro-inflammatory lncRNA-PACER (also known as lncRNA-Cox-2) which is a positive regulator of its proximal pro-inflammatory gene Ptgs- 2 (Also known as Cox-2) ( 25 ).…”
Section: Tuberculosismentioning
confidence: 99%
“…Mtb has developed several strategies to avoid killing within phagocytes. Mtb inhibits the phagosome maturation and autophagy via upregulation of miR-33 locus ( 18 , 26 ), miR-27a-5p ( 18 , 20 ), miR-144-5p and miR-889-5p. Mtb also evades the host defense by Inhibiting macrophage apoptosis ( 27 ) via the upregulation of miR-582-5p ( 28 ).…”
Section: Tuberculosismentioning
confidence: 99%
“…The miRNAs that are associated with pathogenesis of Mtb infection include miR-33/miR-33* ( Ouimet et al., 2016 ), miR-889 ( Chen et al., 2020 ), miR-18a ( Yuan et al., 2020 ), and miR-125a ( Kim et al., 2015 ), all of which are increased by Mtb infection; whereas others such as miR-26a ( Sahu et al., 2017 ) and miR-17-5p ( Kumar et al., 2016 ), both of which are decreased by Mtb infection. Numerous miRNAs that are involved in the regulation of autophagy in terms of host-pathogen interaction during Mtb infection have been extensively discussed elsewhere ( Kim J. K. et al., 2017 ; Sabir et al., 2018 ; Yang and Ge, 2018 ; Silwal et al., 2020 ; Sinigaglia et al., 2020 ) and are not the focus of this Review. Thus, it remains to be fully characterized the exact mechanisms by which Mtb evade from host autophagic defense system, although several autophagy-activating drugs/agents are able to suppress Mtb growth in vitro and in vivo ( Stanley et al., 2014 ; Gupta et al., 2016 ; Paik et al., 2019 ).…”
Section: Overview Of Autophagy During Mycobacterial Infectionmentioning
confidence: 99%